Correlation Between Knowledge Level and Decision to Become A Post-Cesarean IUD Acceptor at Roemani Muhammadiyah Hospital Semarang - Arvy Cahyaningtyas; Qomariyah Qomariyah; Nella Vallen (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
Family planning represents a community-based effort to promote awareness and participation through delaying the age of marriage, regulating births, strengthening family resilience, and improving family welfare to achieve small, joyful, and prosperous families (Suriana et al., 2021). The government targets Couples of Reproductive Age (CRA) to reduce population growth in Indonesia, as CRA consists of legally married couples who actively engage in sexual relations that may result in pregnancy. In addition to CRA, postpartum mothers also serve as a key target group in family planning programs. The “Four Too” components contribute to high-risk pregnancies that may lead to complications during pregnancy, childbirth, and the postpartum period, and maternal and infant mortality. These include being too young (under 20 years), too old (over 35 years), too many children (more than four), and too close birth spacing (less than two years) (Oktarina, 2022). This study employed a quantitative research design, specifically an analytical quantitative approach with a correlational design using the cross-sectional method. The sample consisted of 40 participants. The results show that 45% of respondents had a satisfactory level of knowledge about IUD contraception, 32.5% had a moderate level, and 22.5% had a low level of knowledge. In nursing practice, increasing knowledge about contraception—particularly IUD family planning—can enhance interest in its use. Moreover, the study recommends that husbands provide support for mothers in using IUD contraception.